The Households of Portuguese infantes in the Avis Dynasty: Formation and Autonomy of Alternative Centres of Power in the 16th Century - Carvalhal, Hélder (2021)
The objective of this essay is to discuss the political role of the seigniorial households of the Portuguese infantes (princes) during the sixteenth century, taking into account the degree of autonomy progressively acquired by these individuals and by their respective entourages. I will argue that the households of the infantes were relevant in the territorial and political control of the kingdom during the first half of sixteenth century, namely in the balance of power between nobility and the Crown. Factors such as the existence of a web of interpersonal relationships between the titled nobility or a policy of resource redistribution between the central government and the latter helped the monarchy to control the destination and reproduction of its members, and thus avoided an even greater degree of political division.